Penerapan Lean Manufacturing dengan Menggunakan Value Stream Mapping untuk Mengidentifikasi dan Mengurangi Waste di Gudang PT Manhattan - Marlen Feri Pardosi; Riana Puspita; M. Fazri Pasaribu (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
PT Manhattan is one of the companies engaged in services that provide apartments, supermarkets, cinemas, and food. This research was conducted in a logistics warehouse, where the problem is the problem of time when storing products in the warehouse. Value Stream Mapping is a design method to reduce the time problem so that it gets the best design. The results of the calculation using the Value stream mapping method to get an efficient improvement design from the actual condition. Then 2 activities are part of the value stream mapping and these two activities are included in the category of non-value-added activities. While operational activities include value-added activities, the total time required for value-added activities is 9,660 seconds, while the time required for non-value activities is 5,100 seconds. So the activity mapping process required for value-added activity is 618,890 seconds while the time required for non-value-added activity is 30,520 seconds from the initial condition. With this research, it is expected that logistic warehouses can arrange and use time as quickly and efficiently as possible so that they can facilitate warehouse activities.